Serum neurotrophin profile in systemic sclerosis. - Marie-Claude Lise (Public Library of Science (PLoS), 2010)
Background Neurotrophins (NTs) are able to activate lymphocytes and fibroblasts; they can modulate angiogenesis and sympathic vascular function. Thus, they can be implicated in the three pathogenic processes of systemic sclerosis (SSc). The aims of this study are to determine blood levels of Nerve Growth Factor (NGF), Brain-Derived Neurotrophic Factor (BDNF) and Neurotrophin-3 (NT-3) in SSc and to correlate them with clinical and biological data. Methods Serum samples were obtained from 55 SSc patients and 32 control subjects to measure NTs levels by ELISA and to determine their relationships with SSc profiles. Findings Serum NGF levels were higher in SSc patients (288.26 ± 170.34 pg/mL) than in control subjects (170.34 ± 50.8 pg/mL, p<0.001) and correlated with gammaglobulins levels and the presence of both anti-cardiolipin and anti-Scl-70 antibodies (p<0.05). In contrast, BDNF levels were lower in SSc patients than in controls (1121.9 ± 158.1 vs 1372.9 ± 190.9 pg/mL, p<0.0001), especially in pulmonary arterial hypertension and diffuse SSc as compared to limited forms (all p<0.05). NT-3 levels were similar in SSc and in the control group (2657.2 ± 2296 vs 2959.3 ± 2555 pg/mL, NS). BDNF levels correlated negatively with increased NGF levels in the SSc group (and not in controls). Conclusion Low BDNF serum levels were not previously documented in SSc, particularly in the diffuse SSc subset and in patients with pulmonary hypertension or anti-Scl-70 antibodies. The negative correlation between NGF and BDNF levels observed in SSc and not in healthy controls could be implicated in sympathic vascular dysfunction in SSc.